Aplikasi Berbasis Web untuk Pencatatan Pembelian dan Pemakaian Persediaan Bahan Baku (Studi Kasus: Dadar Bobar, Cibeunying, Kabupaten Bandung, Jawa Barat) - Jihan Maharani, Carina; Yuniar, Irna; Rahmadi (eProceedings of Applied Science, 2025)
Dadar Bobar Restaurant is a culinary business specializing in serving food, particularly egg-based dishes. In its operations, managing raw material inventory is a crucial aspect to ensure the availability of ingredients for production. Therefore, a web-based recording application was developed to facilitate the monitoring of raw material stock, including records of incoming stock, outgoing stock, and remaining inventory. This application is built using the Laravel framework with the PHP programming language and utilizes MySQL as its database. The system is designed to assist the business owner in managing raw material inventory, including tracking stock in and out, estimating material requirements, and generating inventory reports. Keywords: Restaurant, Raw Material Inventory, Laravel, PHP, MySQL